Nocturnal antihypertensive treatment in patients with type 1 diabetes with autonomic neuropathy and non-dipping: a randomised, placebo-controlled, double-blind cross-over trial. Issue 12 (5th December 2016) - Hjortkjær, Henrik Øder; Jensen, Tonny; Kofoed, Klaus F; Mogensen, Ulrik M; Sigvardsen, Per Ejlstrup; Køber, Lars; Hilsted, Karen Lisa; Corinth, Helle; Theilade, Simone; Hilsted, Jannik
Abstract : Objectives: Cardiovascular autonomic neuropathy (CAN) and abnormal circadian blood pressure (BP) rhythm are independent cardiovascular risk factors in patients with diabetes and associations between CAN, non-dipping of nocturnal BP and coronary artery disease have been demonstrated. We aimed to test if bedtime dosing (BD) versus morning dosing (MD) of the ACE inhibitor enalapril would affect the 24-hour BP profile in patients with type 1 diabetes (T1D), CAN and non-dipping. Setting: Secondary healthcare unit in Copenhagen, Denmark. Participants: 24 normoalbuminuric patients with T1D with CAN and non-dipping were included, consisting of mixed gender and Caucasian origin. Mean±SD age, glycosylated haemoglobin and diabetes duration were 60±7 years, 7.9±0.7% (62±7 mmol/mol) and 36±11 years. Interventions: In this randomised, placebo-controlled, double-blind cross-over study, the patients were treated for 12 weeks with either MD (20 mg enalapril in the morning and placebo at bedtime) or BD (placebo in the morning and 20 mg enalapril at bedtime), followed by 12 weeks of switched treatment regimen. Primary and secondary outcome measures: Primary outcome was altered dipping of nocturnal BP. Secondary outcomes included a measurable effect on other cardiovascular risk factors than BP, including left ventricular function (LVF). Results: Systolic BP dipping increased 2.4% (0.03–4.9%; p=0.048) with BD compared to MD of enalapril. There was no increase in mean arterial pressure dipping (2.2% (−0.1% to 4.5%; p=0.07)). No difference was found on measures of LVF (p≥0.15). No adverse events were registered during the study. Conclusions: We demonstrated that patients with T1D with CAN and non-dipping can be treated with an ACE inhibitor at night as BD as opposed to MD increased BP dipping, thereby diminishing the abnormal BP profile. The potentially beneficial effect on long-term cardiovascular risk remains to be determined. Trial registration number: EudraCT2012-002136-90 ; Post-results.